Time domain stochastic finite element simulation towards probabilistic seismic soil-structure interaction analysis - Wang, Fangbo; Sett, Kallol (Soil dynamics and earthquake engineering (1984), 2019)
This paper exploits the recent advances in the field of stochastic finite elements in time-domain simulation of the seismic behavior of soil-foundation-structure systems in three-dimension considering the soil parameters to be heterogeneous, anisotropic, non-Gaussian random fields, structural material parameters to be non-Gaussian random variables, and earthquake motion to be a non-stationary random process. Both the formulation and its implementation are discussed. Scalable numerical schemes for distributed memory parallel computing of hundreds of millions stochastic degrees of freedom, that may arise for any typical uncertain soil-structure interaction (SSI) problem, are presented. Although the presented approach allows for treatment of material nonlinearity, behaviors of only linear systems are illustrated in this study. Through comparisons of the stochastic SSI analysis results with that of the deterministic SSI, deterministic rigid base structural response history, and 1-D deterministic geotechnical site response analyses, and through an extensive parametric study by varying the input uncertainty parameters, the shortcomings of the conventional deterministic approaches are highlighted. •Uncertain seismic wave propagation through uncertain heterogeneous solids in 3D.•Scalable numerical schemes for distributed memory parallel processing.•Comparison of stochastic analyses results with that of the deterministic analyses.•Sensitivity analysis with respect to the input uncertainty parameters.